Injectable hybrid inorganic nanoscaffold as rapid stem cell assembly template for cartilage repair. Issue 4 (28th February 2022) - Wang, Shenqiang; Yang, Letao; Cai, Bolei; Liu, Fuwei; Hou, Yannan; Zheng, Hua; Cheng, Fang; Zhang, Hepeng; Wang, Le; Wang, Xiaoyi; Lv, Qianxin; Kong, Liang; et al.
Abstract: Cartilage injuries are often devastating and most cannot be cured because of the intrinsically low regenerative capacity of cartilage tissues. Although stem-cell therapy has shown enormous potential for cartilage repair, the therapeutic outcome has been restricted by low survival rates and poor chondrocyte differentiation in vivo . Here, we report an injectable hybrid inorganic (IHI) nanoscaffold that facilitates fast assembly, enhances survival and regulates chondrogenic differentiation of stem cells. IHI nanoscaffolds that strongly bind to extracellular matrix (ECM) proteins assemble stem cells through synergistic 3D cell–cell and cell–matrix interactions, creating a favorable physical microenvironment for stem-cell survival and differentiation in vitro and in vivo . Additionally, chondrogenic factors can be loaded into nanoscaffolds with a high capacity, which allows deep, homogenous drug delivery into assembled 3D stem-cell-derived tissues for effective control over the soluble microenvironment of stem cells. The developed IHI nanoscaffolds that assemble with stem cells are injectable. They also scavenge reactive oxygen species and timely biodegrade for proper integration into injured cartilage tissues. Implantation of stem-cell-assembled IHI nanoscaffolds into injured cartilage results in accelerated tissue regeneration and functional recovery. By establishing our IHI nanoscaffold-templated 3D stem-cell assembly method, we provide a promising approach to better overcoming the inhibitory microenvironment associated with cartilage injuries and to advance current stem-cell-based tissue engineering. Abstract : They developed a 3D injectable hybrid inorganic (3D-IHI) nanoscaffold-based approach that significantly accelerated cartilage regeneration in a rabbit critical defect model by improving stem cell survival and chondrogenesis.